Estudo da correlação das características dermatoglífica e somatotípica com as qualidades físicas das atletas de voleibol da Seleção Infanto-juvenil do Estado do Rio Grande do Norte - Cabral, Suzet de Araújo Tinoco (2004)
The purpose of the present study is to identify the dermatoglyphic and somatotypic characteristics and the physical qualities of athletes from the under-17 State volleyball team, in Rio Grande do Norte, Brazil. The sample was composed of athletes, n = 14, aged 15.0 ± 0.88 years, weight (Kg) 58.3 ± 5.90 and height (cm) 169.4 ± 7.97, members of the referred team. For data collection Cummins & Midlo s (1942), o dermatoglyphic method and Heath & Carter s (1967) somatotypic method were used and to evaluate physical qualities, 2400m, 50m, Shuttle Run, abdominal , Sargent test and medicine-ball toss were performed. Fingerprints show that the group presents genetic predisposition for the following physical qualities: explosive force and velocity. As to somatotype, the group was endo-ectomorphic. At physical evaluation the group presented low Vo2 max values and reasonable levels of explosive force, local muscular endurance, agility and velocity. We conclude that: according to the dermatoglyphic model observed, the group needs training strategies to improve coordination and agility; somatotype reveals the necessity for reducing fat levels and increasing muscular mass; the evaluation of physical qualities demonstrates the need for better physical preparation. This study traces the profile of the under-17 volleyball player from Rio Grande do Norte, with respect to genetic and somatotypic aspects and physical qualities, which will serve as a parameter for future state teams